Femtosecond laser inscribed all-in-fiber components for sensing applications - Ioannou, Andreas (Department of Electrical Engineering, Computer Engineering and Informatics, Faculty of Engineering and Technology, Cyprus University of Technology, 2021)
The work presented in the doctoral thesis is directed at the use of femtosecond lasers for the fabrication of novel optical devices and sensors combined with the advantages of telecommunication and specialty optical fibres, as a means to circumvent issues with sensor cross sensitivity, whereby different external effects may be present that act on the fibre sensor preventing “clean” measurements (one that is independent of multiple effects e.g. temperature or axial strain effects). By utilizing the femtosecond laser plane-by-plane inscription technique for the sensor development, components were produced through the inscription of individual planes along the length of the fibre axis, creating multiple complex structures, collocated in the same laser-processed region and enabling the selective measurement of various, potential external perturbations. Considerable effort was put to push the fabrication flexibility offered by the femtosecond laser, with the aim of producing all-in-fibre components providing reliable measurements for chemical sensing and the sensing of physical parameters (temperature, strain, bend, torsion, etc.). In summary, there are several key demonstrations that resulted from the work in this thesis, such as, • the first fs-laser fabrication of tilted fibre Bragg gratings (TFBGs) and controlled excitation of leaky mode resonances (LMRs) in optical fibres • the realisation of surface plasmon devices by combining higher order fs-laser inscribed TFBGs with gold coatings for novel gas sensing devices • a detailed examination of LMRs through the inscription of higher order gratings with small angles triggering the interaction between the fibre’s guided mode and backward coupling to the LMRs, a process that requires tight control of the grating period, reflection angle, order and the strength of the modified refractive index. The tailored-for-LMR-generation optical filters were characterized for torsion, temperature and strain. When compared with the grating response, this led to an exceptionally large strain response and a remarkably well-behaved conversion matrix for the separation of strain and temperature in a single measurement. • fs-laser inscribed optical fibre cladding components to address issues of sensor cross sensitivity, such as strain, bend, temperature, humidity. The inscription method provided immense flexibility and control in the grating fabrication parameters and for the customization of a sensing device and its sensitivity, e.g., tailored bend sensing. This ensures that in contrast to other FBG inscription using a fs laser there was no need to change the laser energy as the device type was changed. This is an important step in the development of compact, smart optical fibre sensors.
Keywords: Optical Fibre Sensors; Femtosecond laser inscription; Fibre Bragg Gratings